2022
DOI: 10.1186/s12943-022-01642-5
|View full text |Cite
|
Sign up to set email alerts
|

S6K1 amplification confers innate resistance to CDK4/6 inhibitors through activating c-Myc pathway in patients with estrogen receptor-positive breast cancer

Abstract: Background CDK4/6 inhibitors combined with endocrine therapy has become the preferred treatment approach for patients with estrogen receptor-positive metastatic breast cancer. However, the predictive biomarkers and mechanisms of innate resistance to CDK4/6 inhibitors remain largely unknown. We sought to elucidate the molecular hallmarks and therapeutically actionable features of patients with resistance to CDK4/6 inhibitors. Methods A total of 36 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…With the use of CDK4/6 inhibitors in preclinical and clinical settings, the relationship between c-Myc and CDK4/6 has been better elucidated. Importantly, c-Myc activation is responsible for both innate [ 66 ] and induced resistance [ 67 , 68 ] to CDK4/6 inhibition therapy. Moreover, the combination of CDK4/6 inhibitors with CDK2 [ 69 , 70 ] or ERK [ 71 ] inhibition can overcome c-Myc-dependent resistance.…”
Section: Discussionmentioning
confidence: 99%
“…With the use of CDK4/6 inhibitors in preclinical and clinical settings, the relationship between c-Myc and CDK4/6 has been better elucidated. Importantly, c-Myc activation is responsible for both innate [ 66 ] and induced resistance [ 67 , 68 ] to CDK4/6 inhibition therapy. Moreover, the combination of CDK4/6 inhibitors with CDK2 [ 69 , 70 ] or ERK [ 71 ] inhibition can overcome c-Myc-dependent resistance.…”
Section: Discussionmentioning
confidence: 99%
“…c-Myc is also activated downstream of kinases such as S6K1. Elevated S6K1 have been reported in 9%–14% of breast cancer patients and studies have demonstrated that elevated S6K1 drives palbociclib resistance via activation of c-Myc signaling pathways in preclinical models and clinical breast cancer samples ( Mo et al, 2022 ).…”
Section: Mechanisms Of Resistance To Combination Cdk4/6 Inhibitor And...mentioning
confidence: 99%
“…Moreover, our analysis also makes predictions about additional protein nodes/interactions that have not yet been identified by the literature. Known mechanisms of resistance to CDK4/6 inhibitors include: Rb loss/mutations [56,57], CDK4/6 overexpression [58][59][60], loss of ER expression [58,61,62], loss of PTEN [63], reduced expression/activity of p21 and p27 [64][65][66], activation of mTOR complexes [67,68], activation of PI3K and PI3K signalling pathways [61,69], activation of PDK1 [70], upregulation of FGFR [71,72], AKT amplification and/or over-activation [73], E2F amplification and/or over-activation [74], MAPK pathway activation [75][76][77], c-Myc activity [78,79], cyclin E overexpression and increased CDK2-cyclin E complex formation [43,44,80,81]. Known mechanisms of resistance to ER inhibitors include mutations that induce the constitutive activation of ER [82,83], loss of ER activity [84,85], activation of PI3K and MAPK signalling [86,87], overexpression of c-Myc [88,89] and loss of p21 and p27 [90,91].…”
Section: The Literature Provides Strong Support For the Predictions M...mentioning
confidence: 99%